Room Temperature Al18F Labeling of 2‐Aminomethylpiperidine‐Based Chelators for PET Imaging. (7th January 2020) - Russelli, Lisa; Martinelli, Jonathan; De Rose, Francesco; Reder, Sybille; Herz, Michael; Schwaiger, Markus; Weber, Wolfgang; Tei, Lorenzo; D'Alessandria, Calogero
Abstract: Positron emission tomography (PET) is a non‐invasive molecular imaging technology that is constantly expanding, with a high demand for specific antibody‐derived imaging probes. The use of tracers based on temperature‐sensitive molecules (i. e. Fab, svFab, nanobodies) is increasing and has led us to design a class of chelators based on the structure of 2‐aminomethylpiperidine (AMP) with acetic and/or hydroxybenzyl pendant arms (2‐AMPTA, NHB‐2‐AMPDA, and 2‐AMPDA‐HB), which were investigated as such for Al 18 F 2+ ‐core chelation efficiency. All the compounds were characterized by HPLC‐MS analysis and NMR spectroscopy. The AlF‐18 labeling reactions were performed under various conditions (pH/temperature), and the radiolabeled chelates were purified and characterized by radio‐TLC and radio‐HPLC. The stability of labeled chelates was investigated up to 240 min in human serum (HS), EDTA 5 mM, PBS and 0.9 % NaCl solutions. The in vivo stability of [Al 18 F(2‐AMPDA‐HB)] − was assessed in healthy nude mice ( n =6). Radiochemical yields between 55 % and 81 % were obtained at pH 5 and room temperature. High stability in HS was measured for [Al 18 F(2‐AMPDA‐HB)] −, with 90 % of F‐18 complexed after 120 min. High stability in vivo, rapid hepatobiliary and renal excretion, with low accumulation of free F‐18 in bones were measured. Thus, this new Al 18 F‐chelator may have a great impact on immuno‐PET radiopharmacy, by facilitating the development of new fluorine‐18‐labeled heat‐sensitive biomolecules. Abstract : Low temp, high yield : A new class of 2‐aminomethylpiperidine‐based chelators was synthesized, characterized, and radiolabeled at room temperature using the Al 18 F method. High labeling yields and high stability in human serum and in vivo for the [Al 18 F(2‐AMPDA‐HB)] − complex were achieved. This chelate can be the basis for the labeling of temperature‐sensitive biomolecules for PET applications.